Trained Immunity-Based Vaccine in B Cell Hematological Malignancies With Recurrent Infections: A New Therapeutic Approach - Ochoa-Grullón, Juliana; Benavente Cuesta, Celina; González Fernández, Ataúlfo; Cordero Torres, Gustavo; Pérez López, Cristina; Peña Cortijo, Ascensión; Conejero Hall, Laura; Mateo Morales, Marta; Rodríguez de la Peña, Antonia; Díez-Rivero, Carmen M.; Rodríguez de Frías, Edgard; Guevara-Hoyer, Kissy; et al. (Frontiers in Immunology, 2021)
Infectious complications are a major cause of morbidity and mortality in B-cell hematological malignancies (HM). Prophylaxis for recurrent infections in HM patients consists of first-line antibiotics and when unsuccessful, gammaglobulin replacement therapy (IgRT). Recent knowledge of trained immunity-based vaccines (TIbV), such as the sublingual polybacterial formulation MV130, has shown a promising strategy in the management of patients with recurrent infections. We sought to determine the clinical benefit of MV130 in a cohort of HM patients with recurrent respiratory tract infections (RRTIs) who underwent immunization with MV130 for 3 months. Clinical information included the frequency of infections, antibiotic use, number of visits to the GP and hospitalizations previous and after MV130 immunotherapy. Improvement on infection rate was classified as: clear (>60% reduction of infection), partial (26-60%) and low (≤25%) improvement. Fifteen HM patients (aged 42 to 80 years; 9 females) were included in the study. Analysis of paired data revealed that the median (range, min - max) of respiratory infectious rate significantly decreased from 4.0 (8.0 – 3.0) to 2.0 (4.0 – 0.0) (p<0.001) at 12 months of MV130. All patients reduced their infection rate. A clear clinical improvement was observed in 53% (n=8) of patients, partial improvement in 40% (n=6) and low improvement in 7% (n=1). These data correlated with a reduce on antibiotic consumption from 3.0 (8.0 – 1.0) to 1.0 (2.0 – 0.0) (p=0.002) during 12 months after initiation of treatment with MV130. The number of infectious-related GP or emergency room visits declined from 4.0 (8.0 – 2.0) to 2.0 (3.0 – 0.0) (p<0.001), in parallel with a reduction in hospital admissions that was also statistically significant (p=0.032). Regarding safety, no adverse events were observed. On the other hand, immunological assessment of IgA and IgG sera levels demonstrated an increase in specific antibody titers following MV130 immunotherapy. In conclusion, MV130, may add clinical benefit reducing the rate of infections and enhancing humoral immune responses in these vulnerable patients.